2022
DOI: 10.53300/001c.33149
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the factors which influence rural nursing and midwifery placement experience: Benefits and challenges identified by students and health service staff

Abstract: Background: Positive rural clinical experiences strongly correlate with future rural health career intention. It is therefore important to understand the factors which contribute to positive rural clinical placement experiences.Aims: To understand the benefits and challenges of rural nursing and midwifery placements for students, and to explore factors which influence positive clinical placement experiences.Methods: Semi-structured interviews were undertaken to explore the experiences and perspectives of nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Students who are satisfied with their clinical placement experiences are more likely to indicate intention to practice in a rural setting than those who have had a negative experience 2,5,9 . There is a growing body of literature regarding the factors which contribute to positive rural placement experiences for health students 2,5,9–11 . Factors include adequate preparation for placement; diversity of rural health experiences; immersion in rural life; support from academic and placement provider staff; placement supervision; and interaction with other students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who are satisfied with their clinical placement experiences are more likely to indicate intention to practice in a rural setting than those who have had a negative experience 2,5,9 . There is a growing body of literature regarding the factors which contribute to positive rural placement experiences for health students 2,5,9–11 . Factors include adequate preparation for placement; diversity of rural health experiences; immersion in rural life; support from academic and placement provider staff; placement supervision; and interaction with other students.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,9 There is a growing body of literature regarding the factors which contribute to positive rural placement experiences for health students. 2,5,[9][10][11] Factors include adequate preparation for placement; diversity of rural health experiences; immersion in rural life; support from academic and placement provider staff; placement supervision; and interaction with other students. Fatima et al 5 identified that social isolation is often a challenge encountered by students during rural placements, which may be a greater challenge for longer placements.…”
mentioning
confidence: 99%